Quality of life of stroke patients during the COVID-19 pandemic - Mello , Luana Franklin; Almeida , Mariana Moskado Batista de; Sambe , Angélica Yumi; Pellizzari, Camila Costa de Araújo; Valenciano , Paola Janeiro; Silva , Joyce Karla Machado da (Seven Editora, 2023)
Introduction: Stroke sequelae can reduce the activity and participation of these individuals, leading to reduced quality of life (QoL). The COVID-19 pandemic changed the organization of society to contain the contamination, leading to the suspension or changes in the format of outpatient care, which may have negatively influenced the QOL and health care of people with stroke. Objective: To analyze the physical, psychological, social relations and environment aspects of the QoL of individuals with stroke during the pandemic and related factors. Methods: This is a cross-sectional study, using an online form and the WHOQOL-Bref questionnaire. Results: Eleven individuals participated in the study, aged between 18 and 80 years, mostly male. Regarding QoL, the psychological domain presented the best score and the physical domain the worst. Likewise, the personal relationships facet the best score and the work ability facet the worst score. Conclusion: During the pandemic, the QoL of people with stroke was impaired. The factors that most interfered were physical condition, work capacity, dependence on medications or treatments, and sexual activity. It is worth mentioning the importance of Physiotherapy in QOL, as it promotes reintegration into the community and maximum capacity of patients. DOI:https://doi.org/10.56238/emerrelcovid19-065